Uji Aktivitas Antioksidan Ekstrak Air dan Ekstrak Etanol Daun Kelor (Moringa Oleifera LAM) - Rizkayanti, Rizkayanti; Diah, Anang Wahid M.; Jura, Minarni Rama (Jurnal Akademika Kimia, 2017)
Moringa (moringa oleifera Lam) leaves contains many molecules as inhibitors for free radicals such as phenolic compounds (phenolic acids, flavonoids, quinones, coumarins, lignans, stilbenes, tannins), nitrogen compounds (alkaloids, amines, betalain), vitamins, terpenoids (including carotenoids), and several other endogenous metabolites as antioxidants. This study aimed to determine the antioxidant potency of water and ethanol extracts of moringa (moringa oleifera Lam) leave obtained by maceration and dekok. The concentration of free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) was analyzed using UV-Vis spectrophotometer after addition of various concentrations of Moringa leaves extracts. Various concentrations of moringa leave extracts used were 20 ppm, 40 ppm, 60 ppm and 80 ppm. Vitamin C solutions as the positive control were prepared on similar various concentrations. The negative control was prepared using DPPH solutions dissolved in absolute ethanol. The results indicated that the ethanol extract of moringa leaves prepared by maceration method showed the antioxidant potency with an IC50 value of 22.1818 ppm, but the IC50 value of water extract of moringa leaves prepared by dekok was 57.5439 ppm. While, the IC50 value of Vitamin C was 8.8084 ppm. Based on the IC50 data it can be concluded that Vitamin C is a stronger antioxidant than moringa leaves extracts.